Community awareness on Coronary Heart Disease in northern areas of Pakistan (Process evaluation of healthy heart program) - Laila Salim (International Journal of Endorsing Health Science Research, 2013)
This document presents data from qualitative research using a series of focus groups which were conducted for the community from 15th April to 30th April 2007. The focus groups were conducted to ascertain the awareness of degree of Coronary Heart Disease (CVD); the quality of the training program, and if behavior has changed as a result of the awareness program, in Northern areas of Pakistan. There were nine focus groups conducted and each group consisted of 6 to 8 participants.All participants in general, reported that they were happy with the awareness program but mentioned that some of the material for health education was not culturally appropriate. Further, all participants were talked about their health behavior and beliefs.The findings suggest that there is a need to focus more on the processes of planning to develop awareness of coronary heart disease (CHD), organize more innovative health education and interventions that aim to empower community to become more informed and active consumers of health care.